Laser nonlinearity compensation for IEEE 802. 11a standard radio over fiber system - Neo Yun Shen, author; Sevia Mahdaliza, author; Idrus, Emad Fathi Aon, author; Proceeding of 2009 IEEE International Conference on Antennas, Propagation and Systems (INAS 2009) 2009 : Johor) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL